Kurang Energi Kronik (KEK) Remaja Putri Pelajar SMU/SMK dI Kabupaten Karangasem Propinsi Bali - Imade Suarjana (Poltekkes Kemenkes Padang, 2020)
The chronic energy deficiency (CED) for reproductive women in Bali is high prevalence. This is a serious problem because they will greatly determine the quality of human resources in the next generations. The purpose study is to determine the risk factors for The CED problem of senior high school students in Karangasem Regency. This study is an observational with a cross sectional design and uses statistical Mantel Haentzel chi square method to determine the significance of risk factors.The results found from fifteen factors suspected of triggering CED in girl teenagers, there were five significant factors, namely the energy intake (OR=2,101; 95% CI=1,295 - 3,409) and protein (OR=0,394; 95% CI=0.241 - 0.644); perceptions of nutrition (OR = 1,942; 95% CI = 1,197 - 3,151); physical activity (1,83; 95% CI =1,029-3,252) and body image (OR = 1,863; 95% CI = 1,133 - 3,062). The prevention of CED need to be intensified by an emphasis on healthy living behaviors that form positive body image. Efforts should also be made to improve diet by increasing the consumption of vegetables and fruits which are the main sources of micronutrient which greatly supports the metabolic processes which are known to run very fast in the period of adolescent growth.